Literacki PR Adama Naruszewicza. Refleksje na marginesach monografii Czytanie Naruszewicza - Magryś, Roman (Dydaktyka Polonistyczna, 2016)
The article is a commentary on the publication mentioned in its title as well as a development ofsome problems brought up in it. The article suggests that the literary image of Naruszewicz should beexamined in the context of a wide spectrum of social, political and historical phenomena in which thewriter was involved. The spectrum, along with the author’s personal relations, is reflected in situationliterature where occasional poetry by Naruszewicz can be placed. The literary PR by Naruszewiczincludes more and less formal texts as well as those in the character of public declarations and, onthe other hand, of a personal nature. The analysis of the writer’s main poetry inclines to correct hisideological image. It seems that he represented the culture of Enlightenment if we accept its modified,leaning to modern times, conservatism.